Fractal Analyzes of Age-Friendly Transportation System: A Comparison of the Istanbul Kadikoy and Besiktas - Göksenin İnalhan; Mohammadamin Fathkabir (Senex: Yaşlılık Çalışmaları Dergisi)
There has been a notable rise in the elderly population and urbanization on a global scale. Urban design plays a crucial role in meeting the demands of the older population and promoting their social engagement and independence. The World Health Organization has published an eight-domain guide to age-friendly cities. Transportation is considered one of the primary concerns highlighted by the WHO. Accessible and reliable transportation helps older adults maintain independence and participate in various social and recreational activities. This research aims to investigate, evaluate, and compare the age-friendliness of urban transportation networksby assessing the complexity and extent of the transportation system using fractal geometry in two particular areas of Istanbul, namely Beşiktaş and Kadıköy. The box-counting analysis was conducted on both the Beşiktaş and Kadıköy public transportation networks in Istanbul, which are part of the age-friendly network, to assess their age-friendliness and efficiency. The findings of this study indicate that the public transportation system in Kadıköy exhibits a greater level of complexity and self-similarity compared to the system in Besiktas. The public transportation system in Kadikoy demonstrates a higher fractal dimension, suggesting a heightened level of connectivity and efficiency compared to the system in Beşiktaş. The findings of this study can be utilized in the context of public transportation to assess its efficacy by identifying its advantages and disadvantages. Consequently, the objective of this approach is to assist policymakers and planners in obtaining a comprehensive understanding of the advantages and disadvantages associated with the existing transportation infrastructure.